Analisis Dampak Ekonomi dan Sosial Penyelenggaraan Kejuaraan Tingkat Nasional VIII Senior–Junior dan Kejuaraan Tingkat Nasional Terbuka II Cadet–Junior Hapkido Indonesia Tahun 2025 di Surabaya - Berlian Chandra Kirana; Tiara Chandra Kirani; Himawan Wismanadi; Aghus Sifaq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the economic and social impacts of the 8th National Senior–Junior Championship and the 2nd National Open Cadet–Junior Hapkido Championship of Indonesia held in Surabaya in 2025. Using official documents, including the event proposal, budget plan, and sponsorship files, this research examines the financing structure, expenditure flows, and projected impacts based on the sport economic impact and multiplier effect frameworks. The findings indicate that the event, which involved more than 617 athletes from 18 provinces, generated approximately IDR 410,000,000 in direct economic impact through spending on accommodation, transportation, food, and local services. With a multiplier value of 1.6, the total economic activity increased to around IDR 656,000,000. Beyond economic benefits, the event also contributed to social cohesion by enhancing community participation, strengthening martial arts networks, and improving Surabaya’s image as a capable host for national sports events. However, the potential economic impact has yet to be fully optimized due to the absence of a post-event reporting system and limited data on informal economic activities. This study concludes that national sports events can serve as strategic instruments to stimulate regional economic growth while reinforcing social capital within local communities.